COMPARATIVE ASSESSMENT OF THE IMMUNE STATUS OF PATIENTS WITH DIABETIC FOOT SYNDROME IN CRITICAL LOWER LIMB ISCHEMIA - Nuraliev, N.A.; Khamdamov, B.Z. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: To study the indicators of the immune system of patients with diabetic foot syndrome (SDS) with signs of critical lower limb ischemia (CINC). Material and methods: 412 patients with diabetic foot syndrome with signs of CINC were monitored, of which 283 (68.7%) were men and 129 (31.3%) were women. Moreover, all examined had a systemic inflammatory response syndrome. 99 patients were urban residents (24.0%), 313 people lived in rural areas (76.0%). The average age of the examined is 62.2 years. The control group consisted of 30 healthy individuals of comparable gender and age. Results: A comparative analysis of the cytokine status in patients with SDS with signs of CINC and healthy individuals showed that the level of both cytokines (IL-17A and IL-10) in patients significantly exceeded the control values, and the trend and direction of changes were the same. Conclusions: The definition of IL-17A has great diagnostic value as an additional test for early diagnosis of complications in patients with diabetes mellitus with signs of CINC.